An investigation of the moderating effect of liquidity on the relationship between debt and financial performance of REITs in Malaysia: An optimal liquidity estimation - Slamet Soedarsono; Sri Mulyani; Hiro Tugiman; Didik Suhardi (Contemporary Economics, 2019)
Numerous studies on Real Estate Investment Trusts (REITs) have claimed that the high dividend payout requirement has constrained the ability of REITs to use internal earnings and that they have to rely on debt financing to support their funding requirements. However, there is also some empirical evidence showing that the use of debt by REITs has adverse effects on the financial performance of REITs. To reconcile the empirical evidence that is obtained from the REITs literature, this study aims to empirically examine how and to what extent the effects of debt on financial performance are contingent on other factors. In this regard, liquidity is hypothesized to moderate the relationship between debt and financial performance and this study will simultaneously estimate the optimal liquidity level that could optimize the financial performance of REITs. The sample for the study consists of all MREITs for the time period from 2005-2016. The study applies the continuous sequential breakpoint threshold regression model specifications of WarpPLS 5.0 (Bai & Perron, 2003; Kock, 2015; Hansen, 2001; Perron, 2006) to analyze the moderating effects of liquidity and the optimal liquidity level on the debt-financial performance relationship, respectively. The findings reveal that the correlation between financial performance and debt is conditioned by liquidity while preserving a certain level of liquidity is negatively related to the debt and financial performance relationship. Thus, an appropriate level of liquidity needs to be maintained to attain the optimal level of liquidity and to optimize financial performance. It is found that each MREITs needs a liquidity level of more than 5.78% of its total net assets to optimize its financial performance. The findings offer a useful guide for MREITs to manage their optimal liquidity level.
Keywords: G29; G30; G32; 330; Debt; Financial Performance; Liquidity; Optimal; REITs